ANALISIS PENINGKATAN KEMAMPUAN LITERASI SAINS SISWA: SEBUAH STUDY METASSYNTESIS - Maulana, Riswandi; Abidin, Zaenal (Jurnal PGSD, 2023)
Abstract Scientific literacy is the ability to be involved with issues related to science, and various scientific ideas, as a reflective citizen, so the assessment of scientific literacy is not merely a measurement of the level of understanding of scientific knowledge but also an understanding of various aspects of the scientific process and the ability to apply knowledge and scientific processes in real situations faced by students. The literature search was carried out on the ERIC electronic database with the keyword "scientific literacy skills" with a total of 130 full text articles, then 20 journals were selected that included increasing students' scientific literacy skills. This research extension strategy includes a systematic literature review type of research using qualitative methods (metasynthesis). The approach in this research is meta-ethnograph. The search results show that scientific literacy skills are skills that need to be improved to serve as the main goal in science education because they are considered to be used to prepare the current generation of students' scientific literacy skills. Many efforts are made to improve scientific literacy skills through various learning methods, approaches, and the influence of teachers in the learning process. Keywords: Scientific Literacy Skills, methods, scientific literacy improvement Abstrak Literasi sains merupakan kemampuan untuk dapat terlibat dengan persoalan yang ada hubungannya dengan sains, dan berbagai gagasan sains, sebagai warga negara yang reflektif, maka penilaian literasi sains tidak semata-mata berupa pengukuran tingkat pemahaman terhadap pengetahuan sains tetapi juga pemahaman terhadap berbagai aspek proses sains serta kemampuan mengaplikasikan pengetahuan dan proses sains dalam situasi nyata yang dihadapi siswa. Penulusuran literature dilakukan pada database elektronik ERIC dengan kata kunci “scientific literacy skill” dengan jumlah 130 artikel full text, kemudian dipilih 20 jurnal yang memuat peningkatan kemampuan literasi sains siswa. Strategi penuluran penelitian ini termasuk jenis penelitian systematic literature review dengan menggunakan metode kualitatif (metas-sintesis). Pendekatan dalam penelitian ini adalah meta-etnograf. Hasil penelusuran menunjukan bahwa keterampilan literasi sains merupakan keterampilan yang perlu ditingkatkan guna dijadikan sebagai tujuan utama dalam pendidikan sains karena dianggap digunakan untuk mempersiapkan generasi masa kini kemampuan literasi sains siswa. Peningkatan kemampuan literasi sains banyak diupayakan melalui berbagai macam metode belajar, pendekatan, dan pengaruh guru dalam proses pembelajaran. Kata Kunci: Scientific Literacy Skills, metode, peningkatan literasi sains